Neuroprotective effects of Lippia javanica (Burm.F.) Spreng. Herbal tea infusion on Lead-induced oxidative brain damage in Wistar rats - Zubair Suleman; Godwill A. Engwa; Mathulo Shauli; Hannibal T. Musarurwa; Ndinashe A. Katuruza; Constance R. Sewani-Rusike (BMC, 2022)
Abstract Background Though Lippia javanica (Burm.f.) Spreng antioxidant activity has been demonstrated, its effect in protecting the brain from lead (Pb)-induced oxidative damage is unknown. This study investigated the effect of L. javanica against Pb-induced oxidative stress, inflammation, apoptosis and acetylcholinesterase activity in rat's brain. Methods L. javanica herbal tea infusion was prepared, its phytochemical constituent was revealed by liquid chromatography-Mass spectrometer (LC-MS) and was administered simultaneously with Pb. Four groups of male Wistar rats (n = 5/group) were used: control received distilled water; Pb-acetate group received 50 mg Pb/ Kg bodyweight (bw), treatment group received 50 mg Pb/ Kg Pb-acetate + 5 ml/kg bw L. javanica and L. javanica group received 5 ml/Kg bw of L. javanica tea infusion only. After 6 weeks of treatment, oxidative status, acetylcholinesterase activity, inflammation and apoptosis was assessed in brain tissue which was also histologically examined. Results Mean brain and heart weight was reduced (p < 0.05) while liver and spleen weights were increased (p < 0.05) in Pb exposed animals but were prevented by L. juvanica treatment. Treatment with L. javanica increased (p < 0.05) overall brain antioxidant status (glutathione and superoxide dismutase activities) and reduced lipid peroxidation (p < 0.05) compared to the Pb exposed animals. Pro-inflammatory cytokine tumour necrotic factor-alpha, pro-apoptosis Bax protein and anticholinesterase activity were reduced (p < 0.05) in Pb-L. javanica treated animals compared to the Pb exposed group. Histological examination confirmed neuroprotective effects of L. javanica as evidenced by reduced apoptosis/necrosis and inflammation-induced vacuolization and oedema in the hippocampus. The L. javanica treatment alone had no detrimental effects to the rats. LC-MS analysis revealed L. javanica to be rich in phenolics. Conclusions This study demonstrated that L. javanica, rich in phenolics was effective in reducing Pb-induced brain oxidative stress, inflammation, apoptosis, acetylcholinesterase activity and neuronal damage.